2021
DOI: 10.1007/s12291-020-00950-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D Status with COVID-19 Infection and Mortality in the Asia Pacific region: A Cross-Sectional Study

Abstract: COVID-19 has been declared a global pandemic by WHO on 11 March 2020. Still, very little is known about the potential protective dietary factors for the prevention of infection and mortality due to COVID-19. Keeping in view the scarcity of literature/studies available, in this regards present study was undertaken to assess if there is any correlation between mean levels of Vitamin D in various Asia Pacific countries with the infection and mortality caused by COVID-19. We collected data for mean levels of Vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(41 reference statements)
4
5
0
Order By: Relevance
“…We have clearly demonstrated that vitamin D insufficiency and deficiency exponentially increase the risk of the disease by a factor of 2.3 to 3.6, even after adjustments for age and sex. However, we did not find any association between low 25(OH)D levels or vitamin D status and excess mortality risk, as observed in previous studies ( 6 , 8 , 11 , 12 ).…”
Section: Discussionsupporting
confidence: 66%
“…We have clearly demonstrated that vitamin D insufficiency and deficiency exponentially increase the risk of the disease by a factor of 2.3 to 3.6, even after adjustments for age and sex. However, we did not find any association between low 25(OH)D levels or vitamin D status and excess mortality risk, as observed in previous studies ( 6 , 8 , 11 , 12 ).…”
Section: Discussionsupporting
confidence: 66%
“…Eating foods enriched in these vitamins had no significant association with lowering the risks of infection. Findings from this study support previous works and add new insights to understand the impact of the application of supplementary medicines in treating COVID-19 [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. This insignificant association of vitamins and mineral taken through different foods with COVID-19 might be due to less absorption during digestion, interaction with other nutrients and elements, and poor digestive systems.…”
Section: Discussionsupporting
confidence: 89%
“…The results indicate that these metal levels are altered in a severity-dependent manner, showing that trace elements place a major role in COVID-19 pathology. Many recent reviews have commented that trace elements, vitamins and heavy metals play a major role in the pathophysiology of COVID-19 due to their pivotal role in homeostasis of the immune and other major systems of the body [22][23][24][25]. In vitro studies showed that SARS-CoV-2 viral spike protein interacts with ACE2 receptor, which is a zinc-dependent peptidyl dipeptide hydrolase.…”
Section: Discussionmentioning
confidence: 99%